UNRAVELING THE WISDOM BEHIND THE TIMELESS SIGNIFICANCE: HITOPADESHA OF EARLY INDIA- (International Journal of Food and Nutritional Sciences, 2022)
Hitopadesha, a classical text of India, provides wisdom through allegoric narratives and moral teachings. The article analyzes the relevance of Hitopadesha in the early Indian social context, its roots, and intends to examine the subjects and contribution of Hitopadesha. The article explores how the Hitopadesha, being considered a fine art form of narration and role modeling through stories, was a guide to various classes for their moral behavior in real life.